Subjective Experiences and Sensitivities in Women with Fibromyalgia: A Quantitative and Comparative Study. (1st April 2018) - De Roa, P.; Paris, P.; Poindessous, J. L.; Maillet, O.; Héron, A.
Abstract : Fibromyalgia is a chronic widespread pain syndrome associated with chronic fatigue. Its pathogenesis is not clearly understood. This study presents subjective experiences and sensitivities reported by fibromyalgia patients, which should be considered in primary care to avoid medical nomadism, as well as stigmatization of the patients. The prevalence of significant characteristics was compared with others patients consulting at the same pain unit who suffer from rebel and disabling form of chronic migraine. Psychometric tests were anonymously completed by 78 patients of the Pain Unit (44 fibromyalgia patients and 34 migraine patients). Tests evaluated pain (Visual Analog scale), childhood traumas (Childhood Trauma Questionnaire), lack of parental affection, stressful life events (Holmes and Rahe Scale), anxiety and depression (Hospital Anxiety and Depression Scale), perceived hypersensitivity to 10 stimuli, and hyperactivity before illness. However, pain scores were comparable in the two groups, and the prevalence was significantly higher in fibromyalgia patients than in migraine patients for anxiety (81.8% versus 51.5%) and depression (57.1% versus 8.8%). Childhood physical abuses were more frequently reported in fibromyalgia than in migraine cases (25% versus 3%). Similarly, the feeling of lack of parental affection, subjective hypersensitivity to stress and stimuli (cold, moisture, heat, full moon, and flavors) or hyperactivity (ergomania), appeared as prominent features of fibromyalgia patients. Fibromyalgia patients considered themselves as being hypersensitive (mentally and physically) compared to migraine patients. They also have higher depression levels. Beyond somatic symptoms, precociously taking account of psychosocial and behavioral strategies would highly improve treatment efficiency of the fibromyalgia syndrome.